2018
DOI: 10.3389/fimmu.2018.02189
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric Systemic Lupus Erythematosus Is Dependent on Sphingosine-1-Phosphate Signaling

Abstract: About 40% of patients with systemic lupus erythematosus experience diffuse neuropsychiatric manifestations, including impaired cognition and depression. Although the pathogenesis of diffuse neuropsychiatric SLE (NPSLE) is not fully understood, loss of brain barrier integrity, autoreactive antibodies, and pro-inflammatory cytokines are major contributors to disease development. Fingolimod, a sphingosine-1-phosphate (S1P) receptor modulator, prevents lymphocyte egress from lymphoid organs through functional anta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 87 publications
(116 reference statements)
0
26
0
Order By: Relevance
“…Balance beam assay for motor coordination was performed 73 on a 1.2 cm round wooden beam after pre-training. The novel object placement test was performed 74 using a 5-min training phase, 4-min testing phase, and short (40 min) or long (90 min) retention intervals. During the testing phase, preference for the new placement was calculated using the following formula: preference for new = (time exploring new placement)/(time exploring new placement + time exploring old placement) × 100% .…”
Section: Methodsmentioning
confidence: 99%
“…Balance beam assay for motor coordination was performed 73 on a 1.2 cm round wooden beam after pre-training. The novel object placement test was performed 74 using a 5-min training phase, 4-min testing phase, and short (40 min) or long (90 min) retention intervals. During the testing phase, preference for the new placement was calculated using the following formula: preference for new = (time exploring new placement)/(time exploring new placement + time exploring old placement) × 100% .…”
Section: Methodsmentioning
confidence: 99%
“…SLE is a chronic autoimmune disease that predominately affects women of childbearing age. Its main features are the autoreactive B and T lymphocytes as well as the overproduction of antibodies targeting self-antigens 69 . Unfortunately, SLE can result in multi-organ pathologies and a wide range of clinical manifestations, including arthritis, central nervous system disease, renal disease and skin disease 70 .…”
Section: Circrnas In Autoimmune Diseasesmentioning
confidence: 99%
“…Nakamura and colleagues previously demonstrated that selective ET A antagonism prevented the progression of lupus nephritis in a murine model (Nakamura, et al, 1995), and more recently, Li Guo and colleagues showed that SLE patients with autoantibodies to ET A were more likely to develop pulmonary hypertension (Guo L, et al, 2015). Although there has not been any clear associations between ET-1 and neuropsychiatric SLE, high concentrations of vascular ET-1 have been observed in vasculitis-prone MRL/lpr mice (Sugimoto, et al, 2017), an established model of SLE (Perry D, et al, 2011), which has been well characterized as a model of spontaneous neuropsychiatric lupus (Gao, et al, 2009;Gulinello & Putterman, 2011;Gulinello, et al, 2012;Stock, et al, 2015;Wen, et al, 2013), with clear leukocyte infiltration to the choroid plexuses and breach of the blood-brain barrier (Mike, et al, 2018).…”
Section: Potential Roles Of the Endothelin-1 Pathway In Central Nervomentioning
confidence: 99%